Videothoracoscopic surgery before and after chest tube drainage for children with complicated parapneumonic effusion, - Rogerio Knebel; Jose Carlos Fraga; Sergio Luis Amantea; Paola Brolin Santis Isolan
Abstract Objectives To evaluate the effectiveness of videothoracoscopic surgery in the treatment of complicated parapneumonic pleural effusion and to determine whether there is a difference in the videothoracoscopic surgery outcome before or after the chest tube drainage. Methods The medical records of 79 children (mean age 35 months) undergoing videothoracoscopic surgery from January 2000 to December 2011 were retrospectively reviewed. The same treatment algorithm was used in the management of all patients. Patients were divided into two groups: in group 1, videothoracoscopic surgery was performed as the initial procedure; in group 2, videothoracoscopic surgery was performed after previous chest tube drainage. Results Videothoracoscopic surgery was effective in 73 children (92.4%); the other six (7.6%) needed another procedure. Sixty patients (75.9%) were submitted directly to videothoracoscopic surgery (group 1) and 19 (24%) primarily underwent chest tube drainage (group 2). Primary videothoracoscopic surgery was associated with a decrease of hospital stay (p = 0.05), time to resolution (p = 0.024), and time with a chest tube (p < 0.001). However, there was no difference between the groups regarding the time until fever resolution, time with a chest tube, and the hospital stay after videothoracoscopic surgery. No differences were observed between groups regarding the need for further surgery and the presence of complications. Conclusions Videothoracoscopic surgery is a highly effective procedure for treating children with complicated parapneumonic pleural effusion. When videothoracoscopic surgery is indicated in the presence of loculations (stage II or fibrinopurulent), no difference were observed in time of clinical improvement and hospital stay among the patients with or without chest tube drainage before videothoracoscopic surgery.